Understanding Digital Signal Processing, Second Edition - Lyons, Richard (Pearson, 2004)
Amazon.com's top-selling DSP book for 5 straight years-now fully updated! Real-world DSP solutions for working professionals! Understanding Digital Signal Processing, Second Edition is quite simply the best way for engineers, and other technical professionals, to master and apply DSP techniques. Lyons has updated and expanded his best-selling first edition-building on the exceptionally readable coverage that made it the favorite of professionals worldwide. This book achieves the perfect balance between theory and practice, making DSP accessible to beginners without ever oversimplifying it. Comprehensive in scope and gentle in approach, keeping the math at a tolerable level, this book helps readers thoroughly grasp the basics and quickly move on to more sophisticated techniques. This edition adds extensive new coverage of quadrature signals for digital communications; recent improvements in digital filtering; and much more. It also contains more than twice as many "DSP Tips and Tricks"... including clever techniques even seasoned professionals may have overlooked. Down-to-earth, intuitive, and example-rich, with detailed numerical exercises Stresses practical, day-to-day DSP implementations and problem-solving All-new quadrature processing coverage includes easy-to-understand 3D drawings Extended coverage of IIR filters; plus frequency sampling, interpolated FIR filters New coverage of multirate systems; including both polyphase and cascaded integrator-comb FIR filters Coverage includes: periodic sampling, DFT, FFT, digital filters, discrete Hilbert transforms, sample rate conversion, quantization, signal averaging, and more.